2014
DOI: 10.1186/s12870-014-0321-4
|View full text |Cite
|
Sign up to set email alerts
|

An aboveground pathogen inhibits belowground rhizobia and arbuscular mycorrhizal fungi in Phaseolus vulgaris

Abstract: BackgroundInduced aboveground plant defenses against pathogens can have negative effects on belowground microbial symbionts. While a considerable number of studies have utilized chemical elicitors to experimentally induce such defenses, there is surprisingly little evidence that actual aboveground pathogens affect root-associated microbes. We report here that an aboveground fungal pathogen of common bean (Phaseolus vulgaris) induces a defense response that inhibits both the belowground formation of root nodule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 56 publications
3
20
1
Order By: Relevance
“…The present study indicated that leaf Xac infection generally reduced root mycorrhizal colonization in the treated seedlings. This agrees with an earlier study in which root AMF colonization decreased in common bean plants ( Phaseolus vulgaris L. ‘Bush Blue Lake’) after infection with the foliar fungus, Colletotrichum gloeosporioides (Ballhorn et al ).…”
Section: Discussionsupporting
confidence: 93%
“…The present study indicated that leaf Xac infection generally reduced root mycorrhizal colonization in the treated seedlings. This agrees with an earlier study in which root AMF colonization decreased in common bean plants ( Phaseolus vulgaris L. ‘Bush Blue Lake’) after infection with the foliar fungus, Colletotrichum gloeosporioides (Ballhorn et al ).…”
Section: Discussionsupporting
confidence: 93%
“…(b) Plants attacked by an aboveground herbivore induce systemic defense responses [herbivore-induced resistance (HIR)] in roots, which have a negative impact on arbuscular mycorrhizal fungi (AMF), reducing the scope for ISR (6,9,28). In addition, systemic induced changes in root exudates can either facilitate or inhibit infection by belowground phytophages.…”
Section: Cross-compartment Signaling and Interactions Induced By Abovmentioning
confidence: 99%
“…Legacies of increased AMF in the soil could benefit the next generation of plants, particularly obligate mycorrhizal species, as is often the case with slow‐growing plants. However, increases in plant defence compounds as the result of aboveground pathogens may also inhibit mutualists (Ballhorn, Younginger, & Kautz, ).…”
Section: Biotic Driversmentioning
confidence: 99%